The liminal impact of lockdown on the Baheliya community. Issue 6 (18th August 2022) - Sarma, Sushanta Kumar; Lalai, Dhwani; Agrawal, Ishan
ABSTRACT: Baheliya, a nomadic tribe, were confined on the outskirts of a village in Madhya Pradesh, India due to the sudden lockdown announced by the government. How does the lockdown impact the nomad community? Using the lens of liminality, this paper details the experience of the community as they struggle between a detached past and an uncertain future. It describes the features of a liminal phase; namely, freedom, egalitarianism, communion, and creativity as experienced by the members from the Baheliya community.